Speech and language biomarkers for Parkinson’s disease prediction, early diagnosis and progression - Fangyuan Cao; Adam P. Vogel; Puya Gharahkhani; Miguel E. Renteria (npj Parkinson's Disease)
Abstract Parkinson’s disease (PD), a multifaceted neurodegenerative disorder, can manifest as an array of motor and non-motor symptoms. Among these, speech and language impairments are particularly prevalent, often preceding motor dysfunctions. Emerging research indicates that these impairments may serve as early disease indicators. In this narrative review, we synthesised current findings on the potential of speech and language symptoms in PD identification and progression monitoring. Our review highlights convergent, albeit preliminary, lines of evidence supporting the value of speech-related features in detecting early or prodromal PD, even across language groups, especially with sophisticated analytical techniques. Distinct speech patterns in PD subtypes and other neurological disorders may assist in differential diagnosis and inform targeted management efforts. These features also evolve over the disease course and could effectively be utilised for disease tracking and guide management plan modifications. Advances in digital voice processing allow cost-effective, remote and scalable monitoring for larger populations.